ANALISIS KOMPARATIF AKSES VASKULAR TERHADAP KEJADIAN HEMATOMA PASCA PERCUTANEOUS CORONARY INTERVENTION DENGAN PEMASANGAN STENT PADA PASIEN ACUTE CORONARY SYNDROME DI RSPAD GATOT SUBROTO - Via Arsita Dewi; Zainal Musthafa; Nurfitri Bustamam (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2015)
Hematoma is the most common non-hearth complication occur in patients after Percutaneous Coronary Intervention (PCI). At Gatot Subroto army center hospital, there are 20% cases of hematoma after PCI reported during the period of January 2014 to December 15th 2014. One of the risk factor of the occurance is the selection of vascular access. This research is conducted to find out the difference between radial and femoral vascular access on hematoma and the lenght of treatment in Acute Coronary Syndrome (ACS) patients after PCI with stent placement using Cross-Sectional design. Data is obtained from medical records of ACS patients that undertook PCI treatment with stent placement. The sample size is calculated using Lemeshow ratio prevalance formula. As many as 75% of the 120 subjects were male, 66.7% aged 45-64 years old and 95% of patients with ACS on-ST Elevation Myocardial Infarction (NSTEMI). Chi-square test show the difference between radial and femoral vascular access after PCI with stent placement on hematoma occurance (p=0,002). However, Fisher test show no difference between radial and femoral vascular access after PCI with stent placement on length of treatment (p=0,116).